Assessing Risk of Disease Progression and Pharmacological Management of Autosomal Dominant Polycystic Kidney Disease: A Canadian Expert Consensus. Issue 1 (1st March 2017) - Soroka, Steven; Alam, Ahsan; Bevilacqua, Micheli; Girard, Louis-Philippe; Komenda, Paul; Loertscher, Rolf; McFarlane, Philip; Pandeya, Sanjaya; Tam, Paul; Bichet, Daniel G.
Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited renal disorder worldwide. The disease is characterized by renal cysts and progressive renal failure due to progressive enlargement of cysts and renal fibrosis. An estimated 45% to 70% of patients with ADPKD progress to end-stage renal disease by age 65 years. Although both targeted and nontargeted therapies have been tested in patients with ADPKD, tolvaptan is currently the only pharmacological therapy approved in Canada for the treatment of ADPKD. The purpose of this consensus recommendation is to develop an evidence-informed recommendation for the optimal management of adult patients with ADPKD. This document focuses on the role of genetic testing, the role of renal imaging, predicting the risk of disease progression, and pharmacological treatment options for ADPKD. These areas of focus were derived from 2 national surveys that were disseminated to nephrologists and patients with ADPKD with the aim of identifying unmet needs in the management of ADPKD in Canada. Specific recommendations are provided for the treatment of ADPKD with tolvaptan.